From Epidemic Meningitis Vaccines for Africa to the Meningitis Vaccine Project - Aguado, M. Teresa (Clin Infect Dis, 2015)
Background. Polysaccharide vaccines had been used to control African meningitis epidemics for >30 years but with little or modest success, largely because of logistical problems in the implementation of reactive vaccination campaigns that are begun after epidemics are under way. After the major group A meningococcal meningitis epidemics in 1996–1997 (250 000 cases and 25 000 deaths), African ministers of health declared the prevention of meningitis a high priority and asked the World Health Organization (WHO) for help in developing better immunization strategies to eliminate meningitis epidemics in Africa. Methods. WHO accepted the challenge and created a project called Epidemic Meningitis Vaccines for Africa (EVA) that served as an organizational framework for external consultants, PATH, the US Centers for Disease Control and Prevention (CDC), and the Bill & Melinda Gates Foundation (BMGF). Consultations were initiated with major vaccine manufacturers. EVA commissioned a costing study/business plan for the development of new group A or A/C conjugate vaccines and explored the feasibility of developing these products as a public–private partnership. Representatives from African countries were consulted. They confirmed that the development of conjugate vaccines was a priority and provided information on preferred product characteristics. In parallel, a strategy for successful introduction was also anticipated and discussed. Results. The expert consultations recommended that a group A meningococcal conjugate vaccine be developed and introduced into the African meningitis belt. The results of the costing study indicated that the “cost of goods” to develop a group A – containing conjugate vaccine in the United States would be in the range of US$0.35–$1.35 per dose, depending on composition (A vs A/C), number of doses/vials, and presentation. Following an invitation from BMGF, a proposal was submitted in the spring of 2001. Conclusions. In June 2001, BMGF awarded a grant of US$70 million to create the Meningitis Vaccine Project (MVP) as a partnership between PATH and WHO, with the specific goal of developing an affordable MenA conjugate vaccine to eliminate MenA meningitis epidemics in Africa. EVA is an example of the use of WHO as an important convening instrument to facilitate new approaches to address major public health problems.